LRP4 Mutations Alter Wnt/beta-Catenin Signaling and Cause Limb and Kidney Malformations in Cenani-Lenz Syndrome - ELÇİOĞLU, HURİYE NURSEL (CELL PRESS, 2010)
Cenani-Lenz syndrome (CLS) is an autosomal-recessive congenital disorder affecting distal limb development. It is characterized mainly by syndactyly and/or oligodactyly and is now shown to be commonly associated with kidney anomalies. We used a homozygosity-mapping approach to map the CLS1 locus to chromosome 11p11.2-q13.1. By sequencing candidate genes, we identified recessive LRP4 mutations in 12 families with CLS. LRP4 belongs to the low-density lipoprotein (LDL) receptor-related proteins (LRPs), which are essential for various developmental processes. LRP4 is known to antagonize LRP6-mediated activation of canonical Wnt signaling, a function that is lost by the identified mutations. Our findings increase the spectrum of congenital anomalies associated with abnormal lipoprotein receptor-dependent signaling.
Keywords: FACIAL DYSMORPHISM; RENAL HYPOPLASIA; LINKAGE ANALYSIS; RECEPTOR; PATHWAYS; COMPLEX; MODELS; FAMILY; TOOL